2016
DOI: 10.15640/jsbed.v4n2a4
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Information and Communication Technology for SMEs in Rural Communities

Abstract: This research examines the significance of information communication technology (ICT) to the growth of Small and Medium Scale Enterprises (SMEs) in rural Ghana using a study of some selected SMEs in the Bawku Municipality in the Upper East region of Ghana. One hundred SMEs were sampled using simple random sampling of small businesses operating in the rural areas within the Bawku municipality. The study found out that ICT has contributed to the growth of SMEs by decreasing cost of communication and transaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The competitive advantage could materialized in the form of capability to produce products and/or services with lower price and better quality from competitors. In the context of SMEs, digital technology, which becomes the main focus of innovation, found to be affecting the firm's performance (Asunka, 2016). It is achieved through reducing communication and transaction cost, and enhancing relationship with consumer and supplier (Hendriarto, 2021;Ansari et al, 2021).…”
Section: Digital Innovation and Competitivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The competitive advantage could materialized in the form of capability to produce products and/or services with lower price and better quality from competitors. In the context of SMEs, digital technology, which becomes the main focus of innovation, found to be affecting the firm's performance (Asunka, 2016). It is achieved through reducing communication and transaction cost, and enhancing relationship with consumer and supplier (Hendriarto, 2021;Ansari et al, 2021).…”
Section: Digital Innovation and Competitivenessmentioning
confidence: 99%
“…In the context of digital transformation, digital capability also significantly giving positive influence to competitive advantage, given the moderation of firm's digital innovation (Adeoye et al, 2019;. Aside from moderating relationship in digital capability, several research found to support the discourse of positive relationship between innovation and competitive advantage (Paladino, 2007;Asunka, 2016;Day, 1999). Based on the explanation above, there are a linking model:…”
Section: Digital Innovation and Competitivenessmentioning
confidence: 99%
“…(Hartono & Halim, 2020;Khin & Ho, 2019). In addition to moderating the relationship between digital capabilities, the discourse on the positive relationship between innovation and company competitiveness is also supported by research conducted by (Asunka, 2016;Hana, 2013). Based on the description of the relationship between variables, the conceptual framework as a model for this research can be seen in Figure 2.…”
Section: Competitivenessmentioning
confidence: 96%
“…In the context of MSMEs, digital technology which is the focal point for digital innovation contributes to the growth of business performance. This contribution was achieved by reducing communication and transaction costs, as well as improving relationships with consumers and suppliers (Asunka, 2016).…”
Section: B Digital Innovationmentioning
confidence: 99%
“…The success of ERP deployment is strongly correlated with the users' adoption behavior (Mayeh et al, 2016). Unfortunately, many logistic industries continue to face low technology adoption rates because of issues with staff incompetence and resistance to fostering innovation (Asunka, 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%